Torsional springback in square section bars of nonlinear work-hardening materials - Dwivedi J.P.; Upadhyay P.C.; Das Talukder N.K. (My University, 2025)
This paper deals with the torsional springback problems of bars of strain-hardening material with arbitrary cross-section. Using the deformation theory of plasticity, a numerical scheme with a Ramberg-Osgood type stress-strain relationship has been prepared which determines the elastic-plastic boundary in addition to springback in the bars. The results have been verified experimentally with mild-steel bars having square cross-section and the experimental results have been found to agree well with the theoretical results obtained numerically. © 1990.